2020
DOI: 10.3390/en13020456
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Electricity Generation from an Array of Subsea Tidal Kite Prototypes

Abstract: Tidal current technologies have the potential to provide highly predictable energy, since tides are driven by lunar cycles. However, before implementing such technologies on a large scale, their environmental performance should be assessed. In this study, a prospective life cycle assessment (LCA) was performed on a 12 MW tidal energy converter array of Minesto Deep Green 500 (DG500) prototypes, closely following the Environmental Product Declaration (EPD) standards, but including scenarios to cover various des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…定义多个功能单位 [42] 或设置不同的预期情景 [38] , 以 便评估新兴技术的变化。敏感性分析可以测试多 个功能单位, 以分析其对结果的影响, 特别是对于 依赖功能单位定义的影响。另一种方法是专注于 研究特定功能, 并提供广泛的技术替代方案 [14] 。 除此之外, 系统边界的选择会影响评价的结果 和比较研究的结论 [17] 。由于使用阶段、 报废阶段、 回 收阶段和使用寿命的数据在技术发展早期是未知 的, 仅有少数研究是从摇篮到坟墓 [43,44] , 无法全面地 评估产品在整个生命周期的环境影响。对于上述 图 5 筛选得到各类论文占比 作为实景数据 [17,45] 。在研究中可以通过在流程图中 使用不同的颜色区分实景数据和背景数据。对于 大多数 LCA, 实景数据和背景数据都是当前数据。 但在前瞻性 LCA 中, 需要考虑到未来技术的发展及 供应链上其他产品或服务的发展, 原始数据非常 有限。 确定实景数据有两种策略: 预测未来情景和假 设极端情景。情景设置的数据来源为文献 [46] 、 专 利 [47] 、 专家访谈 [48] 、 Ecoinvent 数据库 [49][50][51] 、 实验室和试 点工厂结果 [52] 等。情景设置可以通过动态物质流分 析 [44] 、 技术学习曲线 [18] 、 定量过程模拟 [53] 、 经验设计计 算 [54,55] 等方式进行。考虑到前瞻性 LCA 数据的缺失, 同一项研究中可以采用多种数据来源和预测方式。 背景数据通常会随着时间的推移而改变, 所以 需要注意新兴技术在未来发展时背景数据的变化, 同时避免实景数据和背景数据的时间不匹配。背 景数据的确定可以采用和实景数据一样的策略。 即使很多研究阐述了背景数据对前瞻性 LCA 结果 的影响 [13,17,36] , 考虑背景数据动态变化的研究却仍然 较少。Cossutta 等 [52][56] , 通过建立软链接将未来能源组合中的预期效 率收益或者技术分布转移到 LCI 数据库中。当数据 无法获取时, 可以通过神经网络合成数据进行估 计 [57] 。目前, 已有研究对背景数据进行了补充。如 Gibon 等 [58] 使用 Ecoinvent 数据库、 国际能源署的能…”
Section: 技术阶段unclassified
“…定义多个功能单位 [42] 或设置不同的预期情景 [38] , 以 便评估新兴技术的变化。敏感性分析可以测试多 个功能单位, 以分析其对结果的影响, 特别是对于 依赖功能单位定义的影响。另一种方法是专注于 研究特定功能, 并提供广泛的技术替代方案 [14] 。 除此之外, 系统边界的选择会影响评价的结果 和比较研究的结论 [17] 。由于使用阶段、 报废阶段、 回 收阶段和使用寿命的数据在技术发展早期是未知 的, 仅有少数研究是从摇篮到坟墓 [43,44] , 无法全面地 评估产品在整个生命周期的环境影响。对于上述 图 5 筛选得到各类论文占比 作为实景数据 [17,45] 。在研究中可以通过在流程图中 使用不同的颜色区分实景数据和背景数据。对于 大多数 LCA, 实景数据和背景数据都是当前数据。 但在前瞻性 LCA 中, 需要考虑到未来技术的发展及 供应链上其他产品或服务的发展, 原始数据非常 有限。 确定实景数据有两种策略: 预测未来情景和假 设极端情景。情景设置的数据来源为文献 [46] 、 专 利 [47] 、 专家访谈 [48] 、 Ecoinvent 数据库 [49][50][51] 、 实验室和试 点工厂结果 [52] 等。情景设置可以通过动态物质流分 析 [44] 、 技术学习曲线 [18] 、 定量过程模拟 [53] 、 经验设计计 算 [54,55] 等方式进行。考虑到前瞻性 LCA 数据的缺失, 同一项研究中可以采用多种数据来源和预测方式。 背景数据通常会随着时间的推移而改变, 所以 需要注意新兴技术在未来发展时背景数据的变化, 同时避免实景数据和背景数据的时间不匹配。背 景数据的确定可以采用和实景数据一样的策略。 即使很多研究阐述了背景数据对前瞻性 LCA 结果 的影响 [13,17,36] , 考虑背景数据动态变化的研究却仍然 较少。Cossutta 等 [52][56] , 通过建立软链接将未来能源组合中的预期效 率收益或者技术分布转移到 LCI 数据库中。当数据 无法获取时, 可以通过神经网络合成数据进行估 计 [57] 。目前, 已有研究对背景数据进行了补充。如 Gibon 等 [58] 使用 Ecoinvent 数据库、 国际能源署的能…”
Section: 技术阶段unclassified
“…While existing wave energy LCAs are of course particularly relevant, LCAs of other offshore renewables such as tidal stream and offshore wind are also of interest, with considerable similarities in terms of scope and assumptions when modelling project infrastructure and marine operations. In terms of other marine energy LCA studies, very few publications have been produced conducting LCAs of tidal stream projects [11,15,[20][21][22][23]. A particular study of note is Walker et al [20], who compare LCA results…”
Section: Life Cycle Assessment Of Offshore Renewablesmentioning
confidence: 99%
“…A wide range of assumptions for representing marine operations within marine energy LCA studies can be found in the literature. The number of annual operations ranges from 8 times per year for the Pelamis studies [7,12] to less than once a year in one of the tidal stream studies [20], with many studies including planned inspections with smaller vessels [7,12,13,20,23] and some studies representing all marine operations with larger vessels [11,22]. All of the studies only consider planned operations except for two tidal stream LCA studies [22,23], which include a representation of unplanned maintenance within the operating strategies.…”
Section: Representation Of Marine Operationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por fim, uma tecnologia com alguma participação e estudos são as tidal kites, estruturas móveis de subsuperfície ancoradas por cabo a uma poita que apresentam um movimento perpendicular ao fluxo. Dessa forma, uma turbina acoplada em seu corpo irá interagir com uma velocidade relativa da água maior que aquela do fluxo local, aumentando a sua área de extração efetiva (Andersson et al, 2018;Kaddoura et al, 2020;Mademlis et al, 2020).…”
Section: Tecnologias De Extraçãounclassified